Pengujian Antecedents Kepercayaan Konsumen Pada Merek Dan Pengaruhnya Terhadap Loyalitas: Peran Involvement Sebagai Variabel Moderator: Testing - Antecedents of Consumer Trust in a Brand and The Effect to Brand Loyalty.. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract: Three main factors that influence consumer's trust in a brand are: brand characteristics, company's characteristics, and consumer-brand characteristics. This research aims to test the involvement role as a moderating variable and the effect of each antecedent towards consumer's trust on brand and their effect to brand loyalty. The respondents in this research are television and detergent buyers and users who are decision makers and living in Yogyakarta. Respondent choice using purposive sampling technique. Respondents are then divided into two groups: low involvement and high involvement. Validity and reliability testing were conducted in order to figure out the validity rate and data reliability. The result of analisis using simple regression and chow test shows that involvement moderates the relation between brand reputation and brand trust, brand competence and brand trust, company reputation and brand trust, company perceived motives and brand trust, company integrity and brand trust, trust in a company and brand trust, brand-liking and brand trust, brand satisfaction and brand trust, and brand experience and brand trust.